First report on the presence of microplastics in bovine and porcine livers from Costa Rica - Soto-Barrientos, Natalia; Ulate-Naranjo, Karol; Víquez-Murillo, Catalina; García-Rojas, Andrea (Uniciencia, 2026)
[Objective] Given the ease with which microplastics (MPs) are transported, ecosystems around the world are being polluted with these particles. Reports on the presence of MPs in marine organisms are alarming, but research on the presence of such particles in the terrestrial environment is still very scarce in Costa Rica, and even scarcer for the Central American region. Given this situation, it was considered urgent to carry out a multidisciplinary investigation to obtain information about MP contamination of animal tissues destined for human consumption. [Methodology] Samples of 20 livers from bovines and 18 from porcine, were purchased from local markets in 4 of the main meat-producing regions of the country. All samples were chemically digested with potassium hydroxide for the extraction of microplastic particles.. [Results] Ninety percent of the bovine livers were positive for the presence of MPs, as were 83.3% of the porcine livers. Fibers and films, ranging from 220 µm to 4.5 mm, most of which were blue-green in color, were found. [Conclusions] These findings provide information about the types of MPs that were present in the samples analyzed, but they do not aid in determining the exact origin of the particles and how they reached livers of the animals. Nonetheless, it is now clear that these pollutants are reaching human and animal populations, and since adverse effects have already been reported due to the presence of these particles in the human body, these results must be taken into account by healthcare professionals when considering any emerging diseases.